COVID-19 IDD: Findings from a global survey exploring family members' and paid staff's perceptions of the impact of COVID-19 on individuals with intellectual and developmental disabilities (IDD) and their caregivers - Linehan, Christine; Birkbeck, Gail; Araten-Bergman, Tal; Baumbusch, Jennifer; Beadle-Brown, Julie; Bigby, Christine; Bradley, Valerie; Brown, Michael; Bredewold, Femmianne; Chirwa, Masauso; Cui, Jialiang; Godoy Gimenez, Marta; et al. (HRB open research, 2022)
Background: A growing body of evidence attests to the disproportionate impact of COVID-19 on persons with intellectual and developmental disabilities (IDD) during the pandemic. This study asked caregivers about their perceptions of how COVID-19 impacted them and the people they support. Method: An online survey was conducted in 12 countries during August-September 2020 and sought information on demographics, support practices, information and training, experiences of COVID-19, social distancing, and wellbeing, as measured by the DASS12. This study reports on 3,754 family members, direct support professionals, and managers who participated in the survey. Results: Caregivers observed increases in depression/anxiety, stereotyped behaviours, aggression towards others and weight gain in the person(s) they supported. They also reported difficulties supporting the person(s) to access healthcare. Families reported reducing or ceasing employment and absorbed additional costs when supporting their family member. Direct support professionals experienced changes in staff shifts, staff absences, increased workload and hiring of casual staff. Caregivers' wellbeing revealed high levels of stress, depression, and less so anxiety. The strongest predictor of wellbeing among families was observation of changes in mood in the person(s) they supported, while for direct support professionals, the strongest predictors of wellbeing were reorganisation of staff shifts and increases in new direct support staff. Discussion: Findings support the contention of this population experiencing a disproportionate burden during the COVID-19 pandemic, reflecting historical inequities in access to healthcare and other human rights violations which are now protected under the United Nations Convention on the Rights of Persons with Disabilities.
Keywords: Intellectual and Developmental Disability; Caregivers; Health Disparity; Pandemic; Coronavirus; Carers; Intellectual Disability; COVID-19